A new species of Vanilla (Orchidaceae: Vanilloideae) from Brazil - Pansarin, Emerson R.; Miranda, Marcelo R. (Phytotaxa, 2016)
A new orchid species, Vanilla arcuata, native from costal plane (“restinga” vegetation) of the Atlantic rainforests in the State of São Paulo, Brazil is described and illustrated. The relationship of V. arcuata with other related taxa of the genus is discussed.